CPF changes : effects on the old and the ill in Singapore. - Liang, Rebecca Shujuan. (2008)
The main aim of this study was to examine the effects of 5 recent CPF changes on the old and ill in Singapore from the perspective of the public, and determine if they align with the government’s intended objectives for changes.